Representasi Makna Dalam Lirik Lagu “Kita To Kaili” Karya Sanggar Seni Uvemposa - Farhani (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the representation of meaning in the lyrics of the song “Kita To Kaili” by Uvemposa Art Studio, which highlights the beauty and richness of the Kaili culture. By using Stuart Hall's representation theory, this research examines song lyrics through a reflective approach, an intentional approach, and a constructive approach. The data collection technique was done with the method of simak catat, followed by lyric analysis.  The results show that the song lyrics represent the local culture of Palu, especially the culture of the Kaili tribe, the song lyrics represent the cultural and social reality of the Kaili community (reflective approach), convey explicit messages about the cultural identity of the Kaili community (intentional approach), and build a collective narrative about tradition and preservation of local values through the social and cultural processes of the Kaili community (constructive approach).